Modeling of Inverted Pendulum on a Cart by Using Artificial Neural Networks - Korkmaz, Deniz; Bal, Cafer; Gokbulut, Muammer (Ieee, 2015)
In this study, mathematical model of the single bar inverted pendulum on a cart, which exhibits similar behavior to the dynamics of a robotic arm, is derived by using Lagrange method. At the same time, nonlinear model of the inverted pendulum is simulated in MATLAB environment by using Multilayer Artificial Neural Networks (MANN). MANN is trained by back propagation learning algorithm and dynamic NARX network model is selected for MANN. This model is the basis for dynamics of the robotic arm.
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: inverted pendulum; artificial neural networks; lagrange method; nonlinear modeling